Preparation method and application of a vanadium capture additive in catalytic cracking

By preparing a rare earth-free vanadium-capturing additive, the problem of high coke and dry gas yields in the catalytic cracking of heavy oil with high vanadium content was solved, thereby improving the conversion rate and light oil yield, reducing costs and environmental pollution.

CN116966893BActive Publication Date: 2025-11-21PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210432012.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-22
Publication Date
2025-11-21
Estimated Expiration
2042-04-22

AI Technical Summary

Technical Problem

现有催化裂化催化剂在处理高钒含量重油时,焦炭和干气产率高,转化率和轻油收率低,且稀土助剂增加成本和环境污染。

Method used

A rare earth-free vanadium-capturing agent is used, which is prepared from boehmite, clay, metal salt and binder, containing alumina, magnesium oxide and alkaline earth metal oxide. It is formed by spray drying and calcination to form microsphere solids with large specific surface area and suitable pore volume.

Benefits of technology

It significantly improves conversion rate and light oil yield, reduces coke and dry gas yield, slows down vanadium damage to catalyst, and is low in cost and easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003611131200000051
    Figure BDA0003611131200000051
  • Figure BDA0003611131200000061
    Figure BDA0003611131200000061
  • Figure BDA0003611131200000071
    Figure BDA0003611131200000071
Patent Text Reader

Abstract

The application provides a preparation method of a vanadium capturing additive in catalytic cracking and application thereof, and the preparation method comprises the following steps: (1) mixing and beating deionized water, pseudo-boehmite and acid to obtain a slurry; (2) mixing and beating the a slurry and a salt or an oxide of a first alkaline earth metal to obtain a b slurry, wherein the first alkaline earth metal is magnesium; (3) dissolving a salt, an oxide or a hydroxide of a second alkaline earth metal and sodium carboxymethyl cellulose in deionized water to form a gel c, wherein the second alkaline earth metal is one or more of calcium, strontium and barium; (4) mixing and beating the gel c and the b slurry to obtain a d slurry, and then spray drying the d slurry to form microspheres, and then calcining to obtain the vanadium capturing additive. The vanadium capturing additive is a material without rare earth and molecular sieve, has low cost and can slow down the damage of vanadium to a catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic cracking, specifically relating to a method for preparing and applying a vanadium-capturing aid in catalytic cracking. Background Technology

[0002] With the increasing weight of oil refining and the rising content of heavy metal vanadium in feedstock, the performance of catalytic cracking catalysts is being increasingly damaged. Currently, anti-vanadium technology involves adding rare earth metals or rare earth vanadium-capturing agents to the catalyst main agent to resist vanadium.

[0003] US Patent 5603823A discloses a high-content heavy metal vanadium scavenger, which is composed of (a) 15-60 wt% MgO, (b) 30-60 wt% Al2O3 and (c) 10-30 wt% rare earth elements, wherein at least a portion of MgO and Al2O3 form magnesium aluminum spinel, and the rare earth elements are selected from the composition of lanthanum oxide and / or neodymium oxide. The lanthanum / neodymium compound may be lanthanum oxide and / or neodymium oxide formed in the cracking or regeneration stage of the FCC process.

[0004] Chinese patent CN1148256C discloses a magnesium-aluminum spinel composition and its preparation method, which comprises 25-30 wt% magnesium oxide, 60-70 wt% aluminum oxide and 5-15 wt% rare earth metal oxides other than cerium, wherein magnesium and aluminum form a spinel structure, the content of free magnesium oxide is less than 5 wt% of the total composition, and the most probable pore diameter of the composition is not less than 100 angstroms.

[0005] However, the rare earth elements in the aforementioned patented catalysts enhance the amount of strong acid in the catalysts, thereby increasing the yield of coke and dry gas.

[0006] Chinese patent CN104226235A discloses a metal trapping agent and a catalytic cracking method. The agent comprises magnesium hydroxide and / or magnesium oxide in a weight ratio of 5-10:1 to a water-soluble magnesium source. The total amount of magnesium hydroxide and / or magnesium oxide to the water-soluble magnesium source ensures that the prepared metal trapping agent contains 5-95% by weight of magnesium oxide. The amounts of macroporous alumina and microporous alumina ensure that the alumina in the prepared metal trapping agent contains 10-90% by weight of macroporous alumina and 10-90% by weight of microporous alumina. The total amount of macroporous and microporous alumina used results in a total content of 5-90% by weight in the prepared metal catcher; the aluminum phosphate additive contains 15-45% by weight of Al2O3, 50-70% by weight of P2O5, and 0.1-20% by weight of clay on a dry basis, and the aluminum phosphate additive is chlorine-free, with a P to Al weight ratio of 1-5:1. The amount of the aluminum phosphate additive and / or its precursor results in a metal catcher containing 0.5-30% by weight of the aluminum phosphate additive. However, the introduction of high phosphorus content in the aluminum phosphate additive in the above-mentioned metal catcher increases costs and generates phosphorus-containing wastewater during production, polluting the environment.

[0007] Therefore, for processing catalytic cracking feedstocks with high vanadium content, there is a need for a highly efficient vanadium-capturing aid that can be added to catalytic cracking processes, and which can effectively reduce coke and dry gas yields while significantly improving conversion rate, light oil yield, and total liquid yield, thereby enhancing the economic efficiency of catalytic cracking units. Summary of the Invention

[0008] The purpose of this invention is to provide a method for preparing a vanadium-capturing aid in catalytic cracking. Adding this vanadium-capturing aid to the catalytic cracking reaction of heavy oil with high vanadium content can effectively slow down the damage of heavy metal vanadium to the molecular sieve of the main catalyst. It has the characteristics of significantly improving the conversion rate, light oil yield and total liquid yield, while effectively reducing the yield of coke and dry gas.

[0009] Another objective of this invention is to provide an application of a vanadium-capturing auxiliary.

[0010] To achieve the above objectives, the present invention provides a method for preparing a vanadium-capturing aid in catalytic cracking, comprising the following steps:

[0011] (1) Deionized water, boehmite and acid are mixed and pulped to obtain slurry a;

[0012] (2) Mix slurry a with a salt or oxide of a first alkaline earth metal to obtain slurry b, wherein the first alkaline earth metal is magnesium;

[0013] (3) A gel c is formed by dissolving a salt, oxide or hydroxide of a second alkaline earth metal with sodium carboxymethyl cellulose in deionized water, wherein the second alkaline earth metal is one or more of calcium, strontium and barium.

[0014] (4) The gel c is mixed with the slurry b to obtain slurry d. The slurry d is spray-dried to form microsphere solids, and then calcined to obtain vanadium capture agent.

[0015] The method for preparing vanadium capture aid in catalytic cracking according to the present invention further includes adding clay during the pulping process in step (1) and adding a binder during the pulping process in step (2).

[0016] The method for preparing the vanadium-capturing aid in catalytic cracking according to the present invention comprises, based on the total weight of the vanadium-capturing aid as 100%, 20-70 wt% alumina, 25-60 wt% magnesium oxide and 1-20 wt% a second alkaline earth metal oxide.

[0017] The method for preparing the vanadium-capturing aid in catalytic cracking according to the present invention comprises, based on the total weight of the vanadium-capturing aid as 100%, 0.5-14 wt% clay, 20-70 wt% alumina, 25-60 wt% magnesium oxide and 1-20 wt% second alkaline earth metal oxide.

[0018] In the preparation method of the vanadium-capturing aid in catalytic cracking described in this invention, the amount of acid used in step (1) is 18-25% of the weight of boehmite.

[0019] In the preparation method of the vanadium-capturing aid in catalytic cracking described in this invention, the metal molar ratio of sodium carboxymethyl cellulose to the second alkaline earth metal salt in step (3) is 1 to 1.5:1.

[0020] In the preparation method of the vanadium-capturing aid in catalytic cracking described in this invention, the calcination temperature in step (4) is 650-00℃.

[0021] The method for preparing the vanadium-capturing aid in catalytic cracking according to the present invention uses clay that is one or more of kaolin, halloysite, montmorillonite, attapulgite, and acid / alkali-extracting kaolin.

[0022] The method for preparing vanadium-capturing aid in catalytic cracking according to the present invention, wherein the pseudoboehmite is macroporous pseudoboehmite and / or microporous pseudoboehmite, preferably macroporous pseudoboehmite.

[0023] The method for preparing the vanadium-capturing aid in catalytic cracking according to the present invention comprises: the salt of the first alkaline earth metal being magnesium chloride and / or magnesium nitrate; the oxide of the first alkaline earth metal being magnesium oxide; the salt of the second alkaline earth metal being one or more of calcium chloride, strontium nitrate, strontium chloride, barium nitrate, and barium chloride; the oxide of the second alkaline earth metal being calcium oxide; and the hydroxide of the second alkaline earth metal being calcium hydroxide.

[0024] The method for preparing the vanadium-capturing aid in catalytic cracking according to the present invention, wherein the vanadium-capturing aid has a specific surface area greater than 90 m². 2 / g, pore volume is 0.36~0.40cm³ 3 / g, with an average pore size of 12–17 nm and an abrasion index of 0.5–2.4.

[0025] To achieve the above objectives, the present invention also provides an application of the vanadium-capturing aid, wherein the weight ratio of the vanadium-capturing aid to the main catalyst is 1:5.6 to 99, preferably 1:9 to 15.

[0026] The vanadium-capturing aid of the present invention can be physically mixed with the main catalyst and then added to the catalytic cracking unit, or it can be added separately to the catalytic cracking unit and mixed with the catalytic cracking catalyst in the unit.

[0027] Beneficial effects of this invention:

[0028] The vanadium-capturing aid of this invention is a material that does not contain rare earth elements or molecular sieves. It is low in cost and can mitigate the destructive effect of vanadium on catalysts. Using this method to prepare the vanadium-capturing aid can reduce the amount of acid used and improve the wear resistance of boiled eggs. When the catalyst is contaminated with high vanadium content, adding the vanadium-capturing aid of this invention to the catalyst can capture vanadium to generate a highly stable compound, which can mitigate the destructive effect of vanadium on the performance of the main catalyst. This achieves the goal of not only significantly improving the conversion rate, light oil yield, and total liquid yield, but also effectively reducing the yield of coke and dry gas.

[0029] Currently, most vanadium-capturing additives are still in the laboratory exploration stage, with few reports of industrial-scale products. Compared with existing technologies, the vanadium-capturing additive provided by this invention has a specific surface area greater than 90 m². 2 / g, pore volume is 0.36~0.40cm³ 3 / g, with an average pore size of 12–17 nm and an attrition index of 0.5–2.4. This is beneficial for vanadium capture and mass transfer during catalytic cracking reactions. Using rare earth-free and molecular sieve-free raw materials, it was prepared in a pilot-scale device using common boehmite, clay, metal salts, and binders. The process is mature, simple, low-cost, and easy for industrial production. Detailed Implementation

[0030] The present invention will now be described in detail through embodiments. It should be noted that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above description.

[0031] In this invention, the weight on a dry basis refers to the weight after calcination at 800°C for 2 hours.

[0032] In this invention, the solid content of a substance refers to the ratio of its weight after high-temperature calcination to its weight before calcination, i.e., solid content of the substance = 100% - water content of the substance %.

[0033] In this invention, the catalyst-to-oil ratio refers to the mass ratio of the catalyst to the feedstock oil.

[0034] In this invention, unless otherwise specified, ppm means ppm by weight.

[0035] I. Analysis and evaluation methods for the various embodiments and comparative examples of the present invention in the following examples:

[0036] 1. The specific surface area and pore volume of the vanadium capture agent were determined according to the standard method (GB / T5816-1995); the crystallinity retention and wear index were determined according to the standard method of RIPP146-90 (see "Analytical Methods for Petrochemical Products (RIPP Test Methods)", edited by Yang Cuiding, Science Press, 1990).

[0037] 2. The contents of MgO, CaO and V in the vanadium capture aid / catalyst mixture were determined by X-ray fluorescence method.

[0038] 3. The heavy metal vanadium-contaminated catalyst was contaminated according to the following steps: First, appropriate amounts of oxalic acid, ammonium metavanadate, and deionized water were placed on a heating plate, stirred, and heated to 300°C for 30 minutes. After the ammonium metavanadate was completely dissolved, the heating was turned off to obtain a vanadium-contaminated solution. The catalyst was impregnated with different amounts of vanadium-contaminated solution using an equal-volume impregnation method. After stirring evenly, the solution was first heated to 70°C and dried for 4 hours, then heated to 100°C and dried for 12 hours. The dried sample was calcined in a muffle furnace at 550°C for 2 hours to obtain the vanadium-contaminated catalyst.

[0039] 4. All catalysts used for evaluation need to be pre-aged at 800°C and 100% steam for 4 hours.

[0040] 5. The catalytic cracking evaluation conditions of the Advanced Catalytic Cracking Evaluation Unit (ACE) are as follows: the pretreated catalyst sample is placed in the ACE experimental reactor, the reaction temperature is 530℃, the catalyst dosage is 9g, the reaction feedstock is the heavy catalytic cracking feedstock of Lanzhou Petrochemical Company (3 million tons / year), and the catalyst-to-oil ratio is 5.0.

[0041] II. Raw material sources and specifications:

[0042] 1. Kaolin, China Kaolin Corporation, kaolinite content 86% wt%, loss on ignition 20.27% wt%, particle size D(V,0.5), μm=2.131; boehmite, loss on ignition 39.21% wt%; hydrochloric acid, analytical grade, Sichuan Xilong Chemical Co., Ltd.; aluminum sol, alumina content 18.90% wt%.

[0043] 2. Magnesium oxide, analytical grade, Tianjin Guangfu Technology Development Co., Ltd.; Magnesium chloride hexahydrate, analytical grade, Tianjin Kemeio Chemical Reagent Co., Ltd.; Anhydrous calcium chloride, analytical grade, Sinopharm Chemical Reagent Co., Ltd.; Sodium carboxymethyl cellulose (C8H2O) 16 NaO8), food grade, Sinopharm Chemical Reagent Co., Ltd.

[0044] Example 1

[0045] (1) Take 75g of boehmite and add it to 669g of deionized water. Stir for 3 minutes and then add 7.66mL of hydrochloric acid dropwise over 30 seconds. Continue stirring for 30 minutes and then heat the mixture in a water bath to 60℃ and age it for 1 hour to obtain slurry a. (2) Weigh 54.24g of magnesium oxide and 42.99g of aluminum sol and add them to slurry a. Shear the mixture for 3 minutes and then stir for 30 minutes to obtain slurry b. (3) Weigh 23.79g of calcium chloride and 56.4g of sodium carboxymethyl cellulose and add them to 50g of water. Heat and stir for 30 minutes to form calcium gel c. (4) Add gel c to slurry b and stir for 30 minutes to obtain slurry d. Spray dry slurry d to form microsphere solids. Calcine the microsphere solids at 700℃ for 2 hours to obtain vanadium capture agent. The obtained sample is recorded as C1.

[0046] Examples 2-5

[0047] Vanadium-capturing aids C2 to C5 were prepared according to the method in Example 1, and the formulations, preparation parameters, specific surface areas, and pore volumes are listed in Table 1.

[0048] Table 1

[0049]

[0050]

[0051] Comparative Example 1

[0052] This comparative example is used to illustrate the preparation process of the comparative vanadium capture agent D1. According to a vanadium capture agent disclosed in US5603823A, the specific process is as follows: (1) 104.09g of boehmite was added to 798g of deionized water, stirred for 3 minutes, and then 10.63mL of hydrochloric acid was added dropwise over 30 seconds. After stirring for another 30 minutes, the mixture was heated in a water bath to 60℃ and aged for 1 hour to obtain slurry a; (2) 30g of magnesium oxide was weighed and added to slurry a, stirred for 30 minutes, and then sheared for 3 minutes to obtain slurry b; (3) 87.19g of lanthanum chloride hexahydrate was weighed and added to slurry b, stirred for 30 minutes, and then sheared for 3 minutes and stirred for another 30 minutes to obtain slurry c; slurry c was spray-dried to form microsphere solids; the microsphere solids were calcined at 700℃ for 2 hours to obtain the vanadium capture agent, and the obtained sample was recorded as D1.

[0053] Comparative Example 2

[0054] This comparative example is used to illustrate the preparation process of the comparative vanadium-capturing aid D2. (1) 104.09g of boehmite was added to 798g of deionized water, stirred for 3 minutes, and then 10.63mL of hydrochloric acid was added dropwise over 30 seconds. After stirring for another 30 minutes, the mixture was heated in a water bath to 60℃ and aged for 1 hour to obtain slurry a; (2) 30g of magnesium oxide was weighed and added to slurry a, stirred for 30 minutes, and then sheared for 3 minutes to obtain slurry b; (3) 86.72g of cerium nitrate hexahydrate was weighed and added to slurry b, stirred for 30 minutes, and then sheared for 3 minutes and stirred for another 30 minutes to obtain slurry c; slurry c was spray-dried to form microsphere solids; the microsphere solids were calcined at 700℃ for 2 hours to obtain the vanadium-capturing aid, and the resulting sample was recorded as D2.

[0055] Comparative Example 3

[0056] This comparative example is used to illustrate the preparation process of the comparative vanadium-capturing aid D3. According to the conventional method disclosed in CN103785428A, a compound containing magnesium oxide, aluminum oxide and aluminum phosphorus was prepared. (1) 15g of clay and 95.24g of boehmite were added to 858.30g of deionized water. After stirring for 3 minutes, 9.73mL of hydrochloric acid was added dropwise over 30 seconds. After stirring for another 30 minutes, the mixture was heated in a water bath to 60℃ and aged for 1 hour to obtain slurry a. (2) 30g of magnesium oxide was weighed and added to slurry a. After stirring for 30 minutes, the mixture was sheared for 3 minutes to obtain slurry b. (3) 14.98g of aluminum phosphorus compound with a phosphorus to aluminum mass ratio of 1:3 was weighed and added to slurry b. After stirring for 30 minutes, slurry c was spray-dried to form microsphere solids. The microsphere solids were calcined at 700℃ for 2 hours to obtain the vanadium-capturing aid. The obtained sample was recorded as D3.

[0057] Comparative Example 4

[0058] Take 94.71g of boehmite and add it to 778.04g of deionized water. Stir for 3 minutes and then add 9.68mL of hydrochloric acid dropwise. The hydrochloric acid is added over 30 seconds. Continue stirring for 30 minutes and then heat the mixture in a water bath to 60℃ and age it for 1 hour to obtain slurry a. (2) Weigh 50g of magnesium oxide and add it to slurry a. Shear the mixture for 3 minutes and then stir for 30 minutes to obtain slurry b. Spray dry slurry b to form microsphere solids. Calcine the microsphere solids at 700℃ for 2 hours to obtain vanadium capture agent. The obtained sample is recorded as D4.

[0059] Example 6

[0060] A currently used industrial catalytic cracking catalyst was selected as the main catalyst (blank agent, LDC-200 industrial catalyst from Lanzhou Petrochemical Catalyst Plant), denoted as B. The vanadium-capturing aid and main catalyst were mixed at a ratio of 1:9. The mixed catalyst was then subjected to vanadium contamination at 6000 ppm and 8000 ppm using the aforementioned contamination method. The catalytic cracking performance was evaluated on an ACE evaluation unit. The evaluation results are shown in Tables 2 and 3.

[0061] Table 2

[0062]

[0063] In this invention, conversion rate = gasoline yield + liquefied petroleum gas yield + dry gas yield + coke yield, light oil yield = gasoline yield + diesel yield, total liquid yield = gasoline yield + diesel yield + liquefied petroleum gas yield, and coke production factor = ((100 - conversion rate) × coke yield) / conversion rate.

[0064] As can be seen from the data in Table 2, adding the vanadium-capturing aid of this invention to the main catalyst of catalytic cracking can effectively slow down the damage of heavy metal vanadium to the catalytic cracking catalyst, significantly improve the conversion rate, increase the yield of light oil and total liquid yield, and at the same time reduce the yield of coke and dry gas.

[0065] Table 3

[0066]

[0067] Combining the data in Tables 1 and 3, it can be seen that the vanadium-capturing aid provided by this invention has better vanadium-capturing ability in catalytic cracking. In particular, the introduction of an appropriate amount of calcium gel can not only improve the strength of the catalyst and reduce the wear index, but also effectively reduce the yield of coke and dry gas, and improve the yield of light oil and total liquid yield while improving the conversion rate. When the metal capture agent provided by this invention is mixed with the industrial catalytic cracking catalyst at a weight ratio of 1:9, and the vanadium pollution content is 8000 ppm, in the ACE evaluation results under the same reaction conditions, compared with the use of the industrial catalyst alone, the addition of the vanadium capture aid can increase the conversion rate by 5-8 wt%, decrease the heavy oil yield by 3-5 wt%, increase the total liquid yield by 3-6 wt%, decrease the coke selectivity by 0.5-2 wt%, and decrease the dry gas yield by 0.1-0.7 wt%.

[0068] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a vanadium-capturing aid in catalytic cracking, characterized in that, Includes the following steps: (1) Mix deionized water, pseudoboehmite and acid to obtain slurry a; (2) Mix slurry a with a salt or oxide of a first alkaline earth metal to obtain slurry b, wherein the first alkaline earth metal is magnesium; (3) A gel c is formed by dissolving a salt, oxide or hydroxide of a second alkaline earth metal with sodium carboxymethyl cellulose in deionized water, wherein the second alkaline earth metal is one or more of calcium, strontium and barium; (4) The gel c is mixed with the slurry b to obtain slurry d, and the slurry d is spray-dried to form microsphere solids, which are then calcined to obtain vanadium capture agent; In step (3), the molar ratio of sodium carboxymethyl cellulose to the second alkaline earth metal salt is 1~1.5:

1.

2. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, Clay is added during the pulping process in step (1); a binder is added during the pulping process in step (2).

3. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, The vanadium-capturing aid comprises 20-70 wt% alumina, 25-60 wt% magnesium oxide, and 1-20 wt% a second alkaline earth metal oxide, based on 100% of the total weight of the vanadium-capturing aid.

4. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 2, characterized in that, The vanadium-capturing aid comprises 0.5 to 14 wt% clay, 20 to 70 wt% alumina, 25 to 60 wt% magnesium oxide, and 1 to 20 wt% a second alkaline earth metal oxide, based on 100% of the total weight of the vanadium-capturing aid.

5. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, In step (1), the amount of acid used is 18 to 25% of the weight of boehmite.

6. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, The roasting temperature in step (4) is 650~800℃.

7. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 2, characterized in that, The clay is one or more of kaolin, halloysite, montmorillonite, attapulgite, or acid- or alkali-extractable kaolin.

8. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, The pseudoboehmite is macroporous pseudoboehmite and / or microporous pseudoboehmite.

9. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, The salt of the first alkaline earth metal is magnesium chloride and / or magnesium nitrate; the oxide of the first alkaline earth metal is magnesium oxide; the salt of the second alkaline earth metal is one or more of calcium chloride, strontium nitrate, strontium chloride, barium nitrate, and barium chloride; the oxide of the second alkaline earth metal is calcium oxide; and the hydroxide of the second alkaline earth metal is calcium hydroxide.

10. The method for preparing the vanadium-capturing aid in catalytic cracking according to claim 1, characterized in that, The vanadium-capturing aid has a specific surface area greater than 90 m². 2 / g, pore volume 0.36~0.40cm³ 3 / g, with an average pore size of 12~17nm and a wear index of 0.5~2.

4.

11. The application of the vanadium-capturing aid prepared by the preparation method according to any one of claims 1 to 10, characterized in that, The weight ratio of the vanadium-capturing aid to the main catalyst is 1:5.6~99.

12. The application of the vanadium-capturing aid prepared by the method according to claim 11, characterized in that, The weight ratio of the vanadium-capturing aid to the main catalyst is 1:9~15.

Citation Information

Patent Citations

  • Metal chelating agent, preparation method and application thereof, and catalytic cracking method

    CN103785428A

  • Metal trapping agent and catalytic cracking method

    CN104226235A

  • Composition containing Mg-Al spinel and its preparing process

    CN1148256C

  • LA / ND-spinel compositions for metals passivation in FCC processes

    US5603823A

  • Metal chelating agent, preparation method and application thereof, and catalytic cracking method

    CN103789013A